Addressing the barriers to accessing therapy services in rural and remote areas. (19th December 2012) - Dew, Angela; Bulkeley, Kim; Veitch, Craig; Bundy, Anita; Gallego, Gisselle; Lincoln, Michelle; Brentnall, Jennie; Griffiths, Scott
Abstract: Purpose : Throughout the world, people with a disability who live in rural and remote areas experience difficulty accessing a range of community-based services including speech-, physio- and occupational therapy. This paper draws on information gathered from carers and adults with a disability living in a rural area in New South Wales (NSW), Australia to determine the extent to which people living in rural areas may receive a person-centred therapy service. Methods : As part of a larger study in rural NSW into the delivery of therapy services, focus groups and individual interviews were conducted with 78 carers and 10 adults with a disability. Data were analysed using constant comparison and thematic analysis. Results : Three related themes emerged: (i) travelling to access therapy; (ii) waiting a long time to get therapy; and (iii) limited access to therapy past early childhood. The themes overlaid the problems of recruiting and retaining sufficient therapists to work in rural areas. Conclusions : Community-based rehabilitation principles offer possibilities for increasing person-centred therapy services. We propose a person-centred and place-based approach that builds on existing service delivery models in the region and involves four inter-related strategies aimed at reducing travel and waiting times and with applicability across the life course. Implications for Rehabilitation: Therapy service delivery in rural and remote areas requires: Place-based and person centred strategies to build local capacity in communities. Responsive outreach programs working with individuals and local communities. Recognition of the need to support families who must travel to access remotely located specialist services. Innovative use of technology to supplement and enhance service delivery.